PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - Maryanto, - (JI@P, 2017)
This research aimed to analyse the citizenship behavior, and of organizational commitment upon work performance of sub district employees at Gondangrejo Sub-District, Karanganyar Regency. Quantitative research strategy was used to analyse the mentioned research objective. All the employees of the Gondangrejo Sub-District totally 27 employees were selected as the respondents The linear multiple regression was employed to test the research hypothesis. Research result showed that there are effect of leadership style, work environment, organizational citizenship behavior, and organizatinal commitment, partially upon work performance. Research result also indicated that there were impact of those four indenpendent variables simultaneously upun the work performance. Key words: leadership style; work environment; organizational citizenship behavior; organizatinal commitment; work performance.